The effect of the carbonization period to the yield of biomass charcoals of secang, roda, ketapang and siwalan fruits using the small scale PEM A – HRV furnace. (April 2020) - Hatiningrum, W R; Suparno; Huzein, A; Syahputra, R D; Rahangmetang, A D
Abstract: Four kinds of fruit waste in Blora and Tuban, Java Island, still have calorific values which could be harvested as a daily house hold energy source after they turn to charcoals. A small scale carbonization furnace needs to be designed to fulfil this purpose. This research aims at testing an impact of carbonization period to the yield of secang, roda, ketapang and siwalan (skin) fruit charcoals using PEM A-HRV furnace. The furnace was designed only for 4(four) kg in capacity to minimize emission during carbonization. The carbonization temperature was set at 400 ° C with the optimum carbonization period of 4(four) hours in the maximum furnace capacity. A natural draft inlet oxygen system was used for carbonization. The charcoal yielded was between 21.77 % to 32.57 % weight averaged from the 16 times tests. The Calorific values of charcoals vary from 5240 calorie/gram to 6490 calorie/gram (air dry basis) depending on the type of the fruit charcoal. The volatile matter content was still more than 20 % in weight (air dry basis) in the average, saying that the temperature for carbonization needs to be increased even though this may decrease the charcoal yield.